Routines as Shock Absorbers During Organizational Transformation: Integration, Control, and NASA’s Enterprise Information System - Berente, Nicholas; Lyytinen, Kalle; Yoo, Youngjin; King, John Leslie (Organization Science, 2016)
Integration and control are pivotal goals of enterprise information system implementations. However, misalignments inevitably occur between the system and organizational practices, and these misalignments are generally thought to undermine the goals of integration and control. We report on a longitudinal study of NASA’s enterprise information system implementation, and we focus on how misalignments in procurement and project management routines affect integration and control. We show how different elements of routines dynamically adjust over time to enable stable system implementation, increasing integration and control throughout the agency. Greater integration and control on the organizational level were enabled by less-than-complete integration and control at the local level. Dynamically adjusting routines serve as “shock absorbers” that on one hand help promote the stability necessary for organization-wide enterprise-system-driven control and integration, and on the other hand allow for local self-organization.